2018
DOI: 10.1186/s13620-018-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

Towards the development of day one competences in veterinary behaviour medicine: survey of veterinary professionals experience in companion animal practice in Ireland

Abstract: BackgroundVeterinary behaviour medicine should be a foundation subject of the veterinary curriculum because of its wide scope of applications to veterinary practice. Private practitioners are likely to be the primary source of information on animal behaviour for most pet owners, however studies indicate that behavioural issues are not frequently discussed during companion animal consultations and many practitioners lack confidence in dealing with behavioural problems, likely due to poor coverage of this subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
(9 reference statements)
1
24
0
Order By: Relevance
“…Section two presented 10 vignettes, which depicted advice from a veterinary professional (VP or VN) regarding a common feline behaviour. The behavioural problems used in the vignettes were selected by drawing upon recent research by Golden and Hanlon [1] as well as current literature [7,[10][11][12] and the authors' experience. Vignette development is described in Section 2.2.…”
Section: Survey Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Section two presented 10 vignettes, which depicted advice from a veterinary professional (VP or VN) regarding a common feline behaviour. The behavioural problems used in the vignettes were selected by drawing upon recent research by Golden and Hanlon [1] as well as current literature [7,[10][11][12] and the authors' experience. Vignette development is described in Section 2.2.…”
Section: Survey Designmentioning
confidence: 99%
“…Veterinary behavioural medicine (VBM) is an integral aspect of veterinary practice; in particular, for companion animal welfare. However, Golden and Hanlon [1] found that the majority of the veterinary professionals they surveyed in Ireland considered their training to be inadequate in VBM. This was a view shared by respondents in a study by Kogen et al [2] in which only 42.8% reported "a significant amount" of veterinary behaviour training as veterinary students while 39.4% and 17.8% reported receiving "a few hours" and no training respectively, despite the fact that the majority (99.4%) had seen canines or felines with behavioural issues while working in practice.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations